Hubungan Antara Parent and Peer Attachment terhadap Motivasi Belajar Mahasiswa Tingkat Pertama Fakultas Kedokteran Universitas Lampung - Dicky Auliansyah; Dwita Oktaria; Oktafany; Merry Indah Sari (MAJORITY, 2020)
Motivation describes what gets people to do, keeps them doing, and helps them complete. One of the factors that influence motivation is environment. Attachment is an important factor because it is the basis for exploring the environment independently. Parents and friends is considered as an important factor of supporting system in learning. This study aims to determine the relationship between parent and peer attachment on learning motivation. This was an analytic observational study with cross sectional design. There were 157 respondents whose participated in this study. Student attachment was assessed using the Inventory Parent and Peer Attachment and motivation with the Motivated Strategies for Learning Questionnaire. The results showed that 99.4% of respondents had secure attachment and 0.6% had insecure attachment to the parent attachment. 98.1% of respondents had secure attachment and 1.9% had insecure attachment to peer attachment. 3.2% of respondents have low motivation and 96.8% of respondents have high motivation. Statistical analysis using Fisher's test found that there was no relationship between parent attachment and learning motivation (p value = 0.968) and there was no relationship between peer attachment and learning motivation (p value = 0.907). So, it can be concluded that there is no relationship between parent and peer attachment to the learning motivation of first-year students of the Faculty of Medicine, University of Lampung.